Black Canary and Zatanna : Bloodspell - Dini, Paul (DC Comics, 2014)
"Black Canary - Dinah Lance -- mistress of martial arts. Zatanna Zatara - mistress of magic. Heroines, teammates, friends. Now, in this original graphic novel, two of the DC Universe's brightest stars join forces to combat a deadly new threat - a chilling supernatural foe that preys on their weaknesses and unleashes their awesome powers against each other. A year ago, Black Canary infiltrated a gang of female criminals set to pull a dangerous heist at a Las Vegas casino. Its leader was skilled in hand-to-hand combat and with more than a passing interest in the occult, specifically black magic, one nasty customer. Rather than be taken by Canary or the law, she went to her death, vowing she would get revenge on Canary and her own former gang members. Now, a year to the day later, death stalks those gang members, and Canary must turn to her friend Zatanna to help investigate. Two of comics top talents, writer Paul Dini (DETECTIVE COMICS, BATMAN: ARKHAM CITY) and artist Joe Quinones (WEDNESDAY COMICS, TEEN TITANS GO!), bring two of DC Universe's brightest stars togetherin this stunning tale of magic and mayhem"--